Về xây dựng hệ thông tin văn phòng - Viet, Ngo Trung (Journal of Computer Science and Cybernetics, 2018)
Some characteristics of  office information systems are briefly presented in this paper. The user friendly interface problems and methods for text retrieval are discussed in details. Some experiments in implementation of these systems are given.